Oxygen isotope ratios in primate bone carbonate reflect amount of leaves and vertical stratification in the diet. Issue 10 (6th July 2015) - Carter, Melinda L.; Bradbury, Michael W.
Abstract : The stable isotopic biogeochemistry of free‐ranging primates is a unique tool to assess dietary and ecological adaptions among sympatric populations. The present study tested the hypothesis that oxygen isotopes in the bone carbonate of five primate and four ungulate species that live in Kibale National Park, Uganda, would show minimal variability since the species obtain water from a single water source. Bones were analyzed for stable carbon (δ 13 C) and oxygen (δ 18 O) isotope ratios. Results for apatite δ 13 C are consistent with all species feeding in a closed forest habitat and do not exhibit niche partitioning. δ 18 O values, in contrast, cluster by species and correlate positively with the relative contribution of leaves to the whole diet are likely also modified by vertical niche partitioning between taxa within the forest canopy. These results show that biochemical markers from naturally deceased primate remains can aid our understanding of how living animals exploit available resources. Am. J. Primatol. 78:1086–1097, 2016 © 2015 Wiley Periodicals, Inc.